Providing Housing First services for an underserved population during the early wave of the COVID-19 pandemic: A qualitative study. - Cilia Mejia-Lancheros; James Lachaud; Evie Gogosis; Naomi Thulien; Vicky Stergiopoulos; George Da Silva; Rosane Nisenbaum; Patricia O'Campo; Stephen Hwang (PLoS ONE, 2022)
Objective We assessed the critical role of Housing First (HF) programs and frontline workers in responding to challenges faced during the first wave of the COVID-19 pandemic. Method Semi-structured interviews were conducted with nine HF frontline workers from three HF programs between May 2020 and July 2020, in Toronto, Canada. Information was collected on challenges and adjustments needed to provide services to HF clients (people experiencing homelessness and mental disorders). We applied the Analytical Framework method and thematic analysis to our data. Results Inability to provide in-person support and socializing activities, barriers to appropriate mental health assessments, and limited virtual communication due to clients' lack of access to digital devices were among the most salient challenges that HF frontline workers reported during the COVID-19 pandemic. Implementing virtual support services, provision of urgent in-office or in-field support, distributing food aid, connecting clients with online healthcare services, increasing harm reduction education and referral, and meeting urgent housing needs were some of the strategies implemented by HF frontline workers to support the complex needs of their clients during the pandemic. HF frontline workers experienced workload burden, job insecurity and mental health problems (e.g. distress, worry, anxiety) as a consequence of their services during the first wave of the COVID-19 pandemic. Conclusion Despite the several work-, programming- and structural-related challenges experienced by HF frontline workers when responding to the needs of their clients during the first wave of the COVID-19 pandemic, they played a critical role in meeting the communication, food, housing and health needs of their clients during the pandemic, even when it negatively affected their well-being. A more coordinated, integrated, innovative, sustainable, effective and well-funded support response is required to meet the intersecting and complex social, housing, health and financial needs of underserved and socio-economically excluded groups during and beyond health emergencies.